El erotismo en el amor sexual (Journal of Parents and Teachers, 2025)
We approach this topic with curiosity and a desire to learn more about and delve deeper into a reality that is fraught with confusion. In this case, it is a controversial concept, despite the fact that it is something we all experience, as we are all sexual beings who need to live and express ourselves as such. We turn to what “those in the know” have written and then offer some suggestions for educators of adolescent eroticism. “What is natural is the key to what is human”.
Keywords: eroticism, sexuality, pornography, educators, ethics